Cisco Certified Support Technician (CCST) Networking Cert Prep: 3 Connecting Network Devices. - Wallace, Kevin (linkedin.com, 2023)
Prepare for the Cisco Certified Support Technician (CCST) Networking certification with a look at the topics of the exam that relate to connecting network devices.